Effect of Lower-Level Relaxation on the Pulse Generation Performance of Q-Switched Nd:YAG Laser - Fuqiang Ma; Shiyu Wang; Bingbin Li; Peijin Shang; Jinyou Li; Zheyuan Li (Photonics)
When analyzing and designing Q-switched Nd:YAG lasers, the impact of lower-energy-level relaxation on the pulse waveform is often ignored. This approximation typically does not result in significant deviations when the laser pulse duration is much longer than the relaxation time of the lower energy level. However, when the pulse duration approaches the nanosecond range, the spontaneous emission time of lower energy level in the Nd:YAG crystal, which is approximately 30 ns, can severely affect the pulse waveform. In this study, a theoretical model is proposed to investigate the influence of lower-energy-level relaxation on the output pulse waveform of an Nd:YAG laser. Specifically, the output waveform of a narrow-pulse-width Q-switched Nd:YAG laser is simulated. The results indicate that for narrow-pulse-width laser output, lower-energy-level relaxation causes a secondary peak to appear after the main peak of the Q-switched pulse. The energy of this secondary peak is more than two times higher than that of the main peak. An experimental system for acousto-optic Q-switched Nd:YAG lasers has also been established, and the Q-switched pulse waveforms are measured under conditions similar to those in the simulations. The tail peak phenomenon observed in the experiments is consistent with the simulation results, verifying the accuracy of the theoretical model. These findings provide a crucial theoretical foundation for understanding and optimizing Nd:YAG lasers and have significant implications for the development of similar technologies. In laser technology, particularly for applications requiring high precision and performance, considering such factors is essential for optimizing the design and functionality of laser systems.